2010
DOI: 10.1177/0021943610382294
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Learning in Crisis Management

Abstract: All crises emit warning signals. And yet, organizations do not typically see the warnings in time to learn and adapt to prevent a crisis. This conceptual analysis bridges a theoretical gap by connecting current crisis management literature to rhetorical theories that identify barriers to organizational learning. Two connecting models are introduced to outline the barriers to learning, propose the inclusion of learning throughout the crisis cycle, and encourage the adoption of a mindful culture. Previous crisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 85 publications
1
57
0
10
Order By: Relevance
“…In the current research, we focus on how these two dimensions of corporate reputation influence investors' perceptions and reactions at the onset of a crisis, a critical stage in investors' initial attempts to make sense of the crisis (Bundy & Pfarrer, ; Veil, ). The characteristics of the onset of a crisis make the roles of both dimensions of corporate reputation important.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the current research, we focus on how these two dimensions of corporate reputation influence investors' perceptions and reactions at the onset of a crisis, a critical stage in investors' initial attempts to make sense of the crisis (Bundy & Pfarrer, ; Veil, ). The characteristics of the onset of a crisis make the roles of both dimensions of corporate reputation important.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Crisis management models distinguish different stages in crisis management in which different processes take place, approaching crisis management as a cyclical process (cf. Smith, ; Veil, ). In the crisis response stage, the operational response to the crisis is organized, while in the revision stage, it is looked back on what went wrong, how and what changes are to be made (Coombs, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Past research connecting crisis communication to rhetorical theories and methods has focused primarily on the organizational rhetoric surrounding a crisis (Veil, 2011). While Springston, Avery, and Sallot (2010) identified a burgeoning number of articles using rhetorical theory to analyze a crisis situation such as apologia discourse (Hearit & Brown, 2004;Marsh, 2006;Rowland & Jerome, 2004), epideictic discourse (Huxman, 2004), constitutive approach studies (Stokes, 2005), and narrative theory (Heath, 2004), they suggested that Johnson and Sellnow's (1995) return to Aristotle's conceptual framework of available means-and types-of persuasion provided a clear picture of typical crisis communication.…”
Section: Renewal Discoursementioning
confidence: 99%